EKSTRAKSI DAN FRAKSINASI KOMPONEN BIOAKTIF ANTIMIKROBA DALAM BIJI INTISARI DAN DAUN LADA - Lenny Sutedja; Herlina Agustina (Research Center for Chemistry - LIPI, 1994)
In the framework of antimicrobial activity investigation, seeds and leaves of black pepper were fractionated with n-hexane, methanol, chloroform and water consecutively, to isolate the active fractions. The antimicrobial activity was determined by agar plate diffusion method against Staphylococcus aureus ATCC 6536, Escherichia coli ATCC 25922 and Candida albicans ATCC 10231. Antimicrobial activity against the microbes was not found in the pepper leaf extracts as well as in the n-hexane extract of the seeds. Methanol, chloroform and water extracts of pepper seeds showed antimicrobial activity against S.aureus and Calblcans, however they did not show any activity against E.coli. The chloroform extract, which was the most active, was further eluted and fractionated by column chromatography on silica gel, eluted gradually with n-hexanetethylacetate. Antimicrobial activity determination of the fractions obtained from the column chromatography, indicated that fraction L(IV) showed the highest activity. Gas chromatography-mass spectrometry analysis of L(IV) illustrated the possibility of the presence of several compounds, such as piperonal; palmitic acid, stearic acid, oleic acid, B-sitosterol and 2(3H)-furanone, 3,4-bis (l,3-benzodioxol-5-ylmetyl) dihydro.